THE EFFECT OF PRODUCT QUALITY, PRODUCTINNOVATION, AND PROMOTIONAL STRATEGIES ON CONSUMER PURCHASE INTEREST IN EMDE CAKE BUSINESS OF LEMAHBANG SARIREJO LAMONGAN - Ummah Marisatul Hidayah; Mohammad Yaskun; Imam Trisno Edie (Jurnal Scientia, 2023)
The purpose of this research is to determine the effect of product quality, product innovation and promotional strategies on consumer buying interest either partially or simultaneously and the most dominant factor among the three variables above that affect consumer buying interest. The population in this study is the Consumers of UMKM Emde Cake Lemahbang Sarirejo Lamongan, while the number of samples is 76 respondents. And this research uses quantitative methods. From the results of the t-test of the Product Quality variable, it was obtained tcount (4.975) > ttable (1.993), the Product Innovation variable was obtained tcount (2.669) > ttable (1.993), the promotion strategy variable was obtained tcount (3.042) > ttable (1.993). Test results Fcount (62,644) >Ftable (2,732). From the multiple linear regression test Y = 1.162 +0.420X1 +0.176X2 + 0.320X3, it can be seen that the most dominant value is Product Quality of 0.420.